Clinical landscape of LAG-3-targeted therapy. (June 2022) - Chocarro, L.; Blanco, E.; Arasanz, H.; Fernández-Rubio, L.; Bocanegra, A.; Echaide, M.; Garnica, M.; Ramos, P.; Fernández-Hinojal, G.; Vera, R.; Kochan, G.; Escors, D.
Abstract : Lymphocyte-activated gene 3 (LAG-3) is a cell surface inhibitory receptor and a key regulator of immune homeostasis with multiple biological activities related to T-cell functions. LAG-3 is considered a next-generation immune checkpoint of clinical importance, right next to programmed cell death protein 1 (PD-1) and cytotoxic T-cell lymphocyte antigen-4 (CTLA-4). Indeed, it is the third inhibitory receptor to be exploited in human anticancer immunotherapies. Several LAG-3-antagonistic immunotherapies are being evaluated at various stages of preclinical and clinical development. In addition, combination therapies blocking LAG-3 together with other immune checkpoints are also being evaluated at preclinical and clinical levels. Indeed, the co-blockade of LAG-3 with PD-1 is demonstrating encouraging results. A new generation of bispecific PD-1/LAG-3-blocking agents have also shown strong capacities to specifically target PD-1+ LAG-3+ highly dysfunctional T cells and enhance their proliferation and effector activities. Here we identify and classify preclinical and clinical trials conducted involving LAG-3 as a target through an extensive bibliographic research. The current understanding of LAG-3 clinical applications is summarized, and most of the publically available data up to date regarding LAG-3-targeted therapy preclinical and clinical research and development are reviewed and discussed. Highlights: LAG-3 is a highly important next-generation immune checkpoint molecule. Ninety-seven clinical trials are evaluating at least 16 LAG-3-targeting molecules. Here we identify preclinical and clinical studies conducted involving LAG-3. Bispecific LAG-3 molecules are being developed, showing strong capacities. LAG-3/PD-1 co-blockade is demonstrating encouraging results.